Sequentially Catalyzed Three-Component Masuda–Suzuki–Sonogashira Synthesis of Fluorescent 2-Alkynyl-4-(7-azaindol-3-yl)pyrimidines: Three Palladium-Catalyzed Processes in a One-Pot Fashion - Drießen, Daniel; Biesen, Lukas; Müller, Thomas J. J. (Synlett, 2021)
The Masuda–Suzuki–Sonogashira sequence efficiently unites, in a one-pot fashion, a borylation, an arylation, and an alkynylation in the sense of a sequentially Pd-catalyzed three-component reaction to give fluorescent 2-alkynyl-4-(7-azaindol-3-yl) pyrimidines in yields of 24–83% (14 examples). Time-dependent density-functional theory calculations supported the electronic structure of the longest wavelength absorption bands, revealing that this novel consecutive three-component synthesis opens an efficient access to alkynyl meriolins, a novel class of potential inducers of apoptosis.
Keywords: arylation; alkynylation; borylation; fluorescence; multicomponent reaction; meriolins